Edible vegetable oils from oil crops: Preparation, refining, authenticity identification and application. (January 2023) - Wen, Chaoting; Shen, Mengyu; Liu, Guoyan; Liu, Xiaofang; Liang, Li; Li, Youdong; Zhang, Jixian; Xu, Xin
Abstract: With the increase in the world population, the demand for edible oils is increasing. The recommended intake of edible oils by the World Health Organization is 20–25 kg/year, and their intake in impoverished countries is far below the recommended level. Therefore, edible oils not only need to meet the sharply increasing demand of consumers but also need improved quality and diversity. A systematic summary of the extraction, refining, identification of adulteration, digestion and absorption fate and application of edible oils from plants is essential for their further extensive and safe application. Therefore, the sustainable extraction, refining and adulteration identification methods of oils should be summarized. In addition, cooking and digestion processes can affect the composition and quality of oils, and the stability and bioavailability of edible oils need to be improved. This review provides a timely reference for the rational development and design of new types of oils. However, based on current research results, the physical and chemical properties of edible oils from different plant sources, varieties and producing areas need to be compared and classified in the future. Highlights: The production progress of vegetable edible oils from oil crops was described in details. Authenticity identification methods of vegetable edible oils were compared and analyzed. Cooking and digestive process can significantly affect quality of edible vegetable oils. Vegetable edible oils from oil crops exhibited the bright application prospects.